An overview on the state of art on IAH coastal aquifer dynamics and coastal zone website - Sappa, Giuseppe; Ferranti, Flavia (Acque Sotterranee - Italian Journal of Groundwater, 2019)
The website of the IAH Coastal Aquifer Dynamics and Coastal Zone Management (CAD-CZM) Network, linkable at the web address www.iah-cad-czm.net, aims at improving the knowledge about coastal aquifer for supporting worldwide the assessment, development and management of water resources endangered by saltwater intrusion. The overall target of this project is promoting the development of web-GIS that gathers coastal aquifer data from different sources to assist, by the support of researchers, professionals, stakeholders and water managers to make the correct choices for the sustainable use of these precious resources. The CAD-CZM network tries to satisfy the interest expressed in the recommendations issued on different occasions by UNESCO and IAEA for studying coastal areas in the frame of joint programs in cooperation with other international agencies. The CADCZM website structure aims to collect information coming from any kind of source, as technical as scientific, and its target is to make them available in the aim of taking under control the rate of exploitation and the management of these vulnerable groundwater resources. The website organization is like that anyone could find the specific coastal zone, he is interested in gaining information, only looking for it on the google earth link, present inside the website. Once identified the area of interest, it is possible to download, if present, the specific sheet including all the information collected, checked and uploaded, by the scientific committee of the website. Starting from the analysis of a database of more than 70 coastal aquifer, reporting information about lithology, hydrogeological and geochemical characteristics, salinity sources, applied monitoring methods, management strategies, and seawater and brackish groundwater desalination technologies adopted, an updated overview of the state of the knowledge about seawater intrusion all over the world is presented.